Hubungan Pemberian ASI Eksklusif dan MP-ASI dengan Pertumbuhan dan Perkembangan Bayi Usia 6 - 12 Bulan di Wilayah Kerja Puskesmas Harapan Baru Kota Samarinda - Azzah Afifah; Choirul Anna Nur Afifah (Lembaga Pengembangan Kinerja Dosen, 2025)
Breastfeeding (ASI) and complementary feeding (MP-ASI) are determinants of a baby's growth and development starting from the period 0 days or the day after birth until the age of 2 years. Providing nutritional intake that is less than required can cause long-term growth and development in children, which is permanent and difficult to repair. This study aims to determine the relationship between exclusive breastfeeding and MP-ASI with the growth and development of babies aged 6–12 months in the Harapan Baru Community Health Center Working Area, Samarinda City. Type of quantitative research with a cross sectional approach. The location of this research was carried out at the Posyandu in the Working Area of the Harapan Baru Community Health Center, Samarinda City. The sample in this study was mothers of babies 6-12 months with 84 respondents. Data collection was carried out using questionnaires and interviews. The data analysis technique uses the Spearman correlation non-parametric statistical test. The results of the study showed that there was a relationship between giving exclusive breastfeeding and the growth of babies aged 6-12 months (p=0.00), there was a relationship between giving breast milk and the development of babies aged 6-12 months (p=0.021), there was a relationship between giving MP-ASI and growth babies 6-12 months (p=0.022), and there is a relationship between giving MP-ASI and the development of babies 6-12 months (p=0.042). Increasing the provision of appropriate breast milk and MP-ASI is very important to achieve optimal growth and development of babies.